Glycosiled hemoglobin a factor allied in the prevention of post-surgical infection of the diabetic foot: Hemoglobina Glicosilada un factor aliado en la Prevención de Infección Postquirúrgica del Pie Diabético - Villanueva Del Busto, Angela Marcela (2019)
In this work an exhaustive search has been made of studies that show the effect of glycosylated hemoglobin (HbA1c) in the development of post surgical infection in diabetic foot patients. In our country the prevalence of patients with diabetes mellitus reaches up to 8.4%, in this regard it is known that one of the biggest complications of this disease is the development of diabetic foot and that consequently to this pathology up to 20% of these patients end in An amputation, it is also known that patients with diabetes mellitus have a high risk of postoperative complications, including infections, inadequate wound healing, cardiovascular events, venous embolism thrombus, and mortality. Because it has been thought that hyperglycemia mediates this risk, different international studies are carried out that seek to verify and publicize this association, however, because no national studies have been found in this regard, no solid conclusions can be drawn for our population, for which this manuscript aims to motivate the realization of them that reflect the national problem